ANALISIS MATERI PENDIDIKAN LINGKUNGAN HIDUP DALAM BUKU TEKS PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI UNTUK SEKOLAH MENENGAH ATAS - Mohammad Kosim (State Islamic Institute of Madura, 2022)
Abstract: The environment education (PLH) material has almost no place in the Islamic Religious Education and character (PAI-BP) textbooks for senior high school levels. Evidently, in the textbooks for grades 10, 11, and 12, none of the chapters specifically contains PLH. Even if there is PLH material, it is integrated into certain chapters with very limited descriptions. In contrast, the environment is one of the important aspects of Islamic teachings, especially in human relations with other creatures and the natural surroundings. Therefore, preservingÂ in an Islamic perspective, the environment is not only a noble act but also rewarding worship. On the other hand, destroying the environment is not just an act of violation but also a sin that is threatened with punishment. For this reason, the government needs to revise the curriculum in order to adequately increase the content of PLH material in PAI-BP lessons. This, in the short term, aims to overcome the shortage of PLH materials, PAI-BP teachers need to optimize PLH through habituation, providing examples of clean living and clean environmental activities.